A Guideline for Life Cycle Assessment of Carbon Capture and Utilization - Müller, Leonard Jan; Kätelhön, Arne; Bachmann, Marvin; Zimmermann, Arno; Sternberg, André; Bardow, André (Frontiers in Energy Research, 2020)
Carbon Capture and Utilization (CCU) is an emerging field proposed for emissions mitigation and even negative emissions. These potential benefits need to be assessed by the holistic method of Life Cycle Assessment (LCA) that accounts for multiple environmental impact categories over the entire life cycle of products or services. However, even though LCA is a standardized method, current LCA practice differs widely in methodological choices. The resulting LCA studies show large variability which limits their value for decision support. Applying LCA to CCU technologies leads to further specific methodological issues, e.g., due to the double role of CO2 as emission and feedstock. In this work, we therefore present a comprehensive guideline for LCA of CCU technologies. The guideline has been development in a collaborative process involving over 40 experts and builds upon existing LCA standards and guidelines. The presented guidelines should improve comparability of LCA studies through clear methodological guidance and predefined assumptions on feedstock and utilities. Transparency is increased through interpretation and reporting guidance. Improved comparability should help to strengthen knowledge-based decision-making. Consequently, research funds and time can be allocated more efficiently for the development of technologies for climate change mitigation and negative emissions.